Program Holistik KELILING Berbasis TOGA untuk Pemberdayaan Lingkungan dan Ekonomi Warga Kampung Cumpat Surabaya - Himmatul Mursyidah; Indah Rosidah; Ardiyani Sekarningrum; Tria Amalia; Dharul Jannah (Universitas Muhammadiyah Banten, 2026)
The KELILING holistic program (EduGreen Village Environmental Empowerment Solution) was implemented in Cumpat Village, Kedung Cowek Urban Village, Bulak District, Surabaya City, to address environmental issues caused by limited green spaces and low community capacity in plant cultivation. This community service program aimed to provide education, training, and mentoring on the cultivation and processing of Family Medicinal Plants (Tanaman Obat Keluarga—TOGA) for residents of RT 03, RT 04, and RT 05, RW 02. The methods employed included discussions, training sessions, practical activities, and continuous mentoring. The program resulted in increased community knowledge and skills in cultivating TOGA on limited land through the use of pots and vertical planting systems. A total of 300 TOGA plants were distributed and planted in residents’ home yards. In addition, participants were trained to process TOGA into value-added products, such as herbal drinks and ginger cookies, which have the potential to generate additional household income. The program also encouraged community participation in environmental greening efforts and supported the development of Cumpat Village as a TOGA-based green village. Overall, the program contributed to environmental improvement, community empowerment, and the enhancement of local economic capacity.